Pathogen dynamics and discovery of novel viruses and enzymes by deep nucleic acid sequencing of wastewater - Wyler, Emanuel; Lauber, Chris; Manukyan, Artür; Deter, Aylina; Quedenau, Claudia; Teixeira Alves, Luiz Gustavo; Wylezich, Claudia; Borodina, Tatiana; Seitz, Stefan; Altmüller, Janine; Landthaler, Markus (Environment international, 2024)
Wastewater contains an extensive reservoir of genetic information, yet largely unexplored. Here, we analyzed by high-throughput sequencing total nucleic acids extracted from wastewater samples collected during a 17 month-period in Berlin, Germany. By integrating global wastewater datasets and applying a novel computational approach to accurately identify viral strains within sewage RNA-sequencing data, we demonstrated the emergence and global dissemination of a specific astrovirus strain. Astrovirus abundance and sequence variation mirrored temporal and spatial patterns of infection, potentially serving as footprints of specific timeframes and geographical locations. Additionally, we revealed more than 100,000 sequence contigs likely originating from novel viral species, exhibiting distinct profiles in total RNA and DNA datasets and including undescribed bunyaviruses and parvoviruses. Finally, we identified thousands of new CRISPR-associated protein sequences, including Transposase B (TnpB), a class of compact, RNA-guided DNA editing enzymes. Collectively, our findings underscore the potential of high-throughput sequencing of total nucleic acids derived from wastewater for a broad range of applications.
Online verfügbar: 8. Juli 2024, Artikelversion: 14. Juli 2024
Gesehen am 03.02.2025